2007
DOI: 10.1111/j.1460-9568.2007.05869.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced insulin‐induced phosphatidylinositol‐3‐kinase activation in peripheral blood mononuclear leucocytes from patients with Alzheimer's disease

Abstract: The epidemiological finding of an increased risk of dementia in patients with diabetes mellitus has raised the hypothesis that a dysfunction of the insulin receptors plays a role in the pathogenesis of Alzheimer's disease (AD). A possible link is suggested by the evidence that the insulin-stimulated phosphatidylinositol-3-kinase (PI-3-K)/phospho-Akt pathway negatively controls the glycogen synthase kinase-3beta. The activation of this enzyme mediates the hyperphosphorylation of the tau protein, a relevant step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Together with the 20 genes mapped to the Insulin signalling pathway KEGG hsa04910 (ACACA, CALM1, CALM3, EIF4E2, FOXO1A, INSR [110], [111], [112], [113], [114], [115], [116], [117], MAPK1, PDE3A, PHKA2, PIK3R1, PIK3R4, PPP1CC, PRKAR2A, PRKAR2B, PRKCI, RHEB, RHOQ, RPS6KB2, SKIP, and TSC2), our results seem to give some support to the hypothesis of altered calcium dynamics [35], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], deregulation of insulin signalling [36], [41], [113], [114], [115], [116], [128], [129], [130], [131], [132], [133], [134], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146], [147], [148], [149], [150], [151], [152], [153], [154], [155], [156], [157], [158], [159], [160], [161], [162], [163]…”
Section: Resultssupporting
confidence: 80%
“…Together with the 20 genes mapped to the Insulin signalling pathway KEGG hsa04910 (ACACA, CALM1, CALM3, EIF4E2, FOXO1A, INSR [110], [111], [112], [113], [114], [115], [116], [117], MAPK1, PDE3A, PHKA2, PIK3R1, PIK3R4, PPP1CC, PRKAR2A, PRKAR2B, PRKCI, RHEB, RHOQ, RPS6KB2, SKIP, and TSC2), our results seem to give some support to the hypothesis of altered calcium dynamics [35], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], deregulation of insulin signalling [36], [41], [113], [114], [115], [116], [128], [129], [130], [131], [132], [133], [134], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146], [147], [148], [149], [150], [151], [152], [153], [154], [155], [156], [157], [158], [159], [160], [161], [162], [163]…”
Section: Resultssupporting
confidence: 80%
“…We used PBMCs as a surrogate system as lymphocytes in PBMCs express receptors, intracellular signaling proteins, and enzymes that are regulated by many of the same genetic and environmental influences as neurons in the brain (Gladkevich et al , 2004; Tsuang et al , 2005). The expression levels of many classes of biologically relevant processes are similar in PBMCs and brain (Sullivan et al , 2006), as may be the case with GSK3 and its regulatory signaling pathways (Castri et al , 2007; Li et al , 2007a), making PBMCs a valuable human tissue to study signaling systems that also occur in human brain. However, it is clear that further studies are needed to clarify the relationships between the activities of signaling systems in PBMCs and the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover several studies have reported an increased risk of dementia in subjects with non-insulin-dependent diabetes mellitus [50]. In order to test this hypothesis, Castri et al [51] analyzed the PI3K/Akt pathway following an in vitro challenge with insulin in peripheral blood mononuclear cells from patients with Alzheimer's disease compared with normal controls. Their major finding is that activation of the PI3K pathway was blunted in the peripheral cells from all of the patients with Alzheimer's disease, independent of the extent of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%